A Novel Concept of a Cartoon-Generator Application on a Mobile Phone - Stergar, Janez; Šuli?, Andrija; Silva, Bruno Rodrigues (International Journal of Interactive Mobile Technologies (iJIM), 2010)
In this work the development and deployment of a new concept of cartoon-generation on a mobile phone is presented. An interactive multimedia application was designed for a push-approach of sending short e-cartoons from a mobile phone to a central WEB server. The concept of a unique cartoon-generator will be discussed. The multimedia Authoring Environment Flash was used for the interactive application design and implementation. The architecture and the design process of the interactive cartoon-generator application will be presented including storyboarding with final testing of the application on a Nokia mobile phone.